2022
DOI: 10.1161/circresaha.121.319915
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Sex and Gender on Stroke

Abstract: Women face a disproportionate burden of stroke mortality and disability. Biologic sex and sociocultural gender both contribute to differences in stroke risk factors, assessment, treatment, and outcomes. There are substantial differences in the strength of association of stroke risk factors, as well as female-specific risk factors. Moreover, there are differences in presentation, response to treatment, and stroke outcomes in women. This review outlines current knowledge of impact of sex and gender on stroke, as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
143
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 242 publications
(201 citation statements)
references
References 187 publications
(300 reference statements)
4
143
0
6
Order By: Relevance
“…Fourth, recent studies have illustrated the gender differences on the inflammation response. Although our results indicated that there was no significant difference in the prognostic role of neutrophils in ABAO patients, further analysis was limited due to the relatively small number of female patients ( 31 ). Due to the real-world design of the present study, we cannot specifically control for gender ratio when enrolling patients.…”
Section: Discussionmentioning
confidence: 61%
“…Fourth, recent studies have illustrated the gender differences on the inflammation response. Although our results indicated that there was no significant difference in the prognostic role of neutrophils in ABAO patients, further analysis was limited due to the relatively small number of female patients ( 31 ). Due to the real-world design of the present study, we cannot specifically control for gender ratio when enrolling patients.…”
Section: Discussionmentioning
confidence: 61%
“…Gender [39]: This feature refers to the participant's gender. The number of men is 1260, whereas the number of women is 1994.…”
mentioning
confidence: 99%
“…29 The epidemiology of stroke in women was reviewed extensively in 2022 in Circulation Research. 8 As this review underscored, the lifetime risk of stroke is 25.1% in women and 24.7% in men, and women face a disproportionate burden of stroke mortality and disability.…”
Section: Clinical Cvd and Cardiovascular Mortalitymentioning
confidence: 92%